Post-Disaster Reconstruction Assistance of Iwate University through Government -University-Industry Collaboration - OGAWA, Kaoru (Journal of the Japan Society for Intellectual Production, 2011)
When the monster March 11 tsunami wiped out towns all along the Sanriku coast, thousands of people in Iwate Prefecture lost their lives and their daily work. Since the Great Eastern Japan Earthquake, Iwate University has been developing support people and industry affected by the disaster through government-university-industry collaboration. This paper reviews the post-disaster reconstruction assistance of Iwate University which has been making good use of a human network of Iwate Network System (INS).